Upscaling of hiPS Cell–Derived Neurons for High-Throughput Screening. (March 2017) - Traub, Stefanie; Stahl, Heiko; Rosenbrock, Holger; Simon, Eric; Heilker, Ralf
The advent of human-induced pluripotent stem (hiPS) cell–derived neurons promised to provide better model cells for drug discovery in the context of the central nervous system. This work demonstrates both the upscaling of cellular expansion and the acceleration of neuronal differentiation to accommodate the immense material needs of a high-throughput screening (HTS) approach. Using GRowth factor–driven expansion and INhibition of NotCH (GRINCH) during maturation, the derived cells are here referred to as GRINCH neurons. GRINCH cells displayed neuronal markers, and their functional activity could be demonstrated by electrophysiological recordings. In an application of GRINCH neurons, the brain-derived neurotrophic factor (BDNF)–mediated activation of tropomyosin receptor kinase (TrkB) was investigated as a promising drug target to treat synaptic dysfunctions. To assess the phosphorylation of endogenous TrkB in the GRINCH cells, the highly sensitive amplified luminescent proximity homogeneous assay LISA (AlphaLISA) format was established as a primary screen. A high-throughput reverse transcription (RT)–PCR format was employed as a secondary assay to analyze TrkB-mediated downstream target gene expression. In summary, an optimized differentiation protocol, highly efficient cell upscaling, and advanced assay miniaturization, combined with increased detection sensitivity, pave the way for a new generation of predictive cell-based drug discovery.